Rattus timorensis Kitchener, Aplin & Boeadi 1991 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
098. Timor Forest Rat Rattus timorensis French: Rat de Timor / German: Timor-Ratte / Spanish: Rata de bosque de Timor Other common names: Timor Rat Taxonomy. Rattus timorensis Kitchener, Aplin & Boeadi, 1991, 7 km east of Desa Nenas, 1900 m, Gunung Mutis, Timor, Nusa Tenggara, Indonesia. Phylogenetic affinities of R. timorensis are unclear, but based on albumin immunological analysis and unpublished allozyme electrophoresis, it is related to Komodomys rintjianus and Bunomys chrysocomus, although most closely to K. rintjianus. This implies that R. timorensis should be included in a different genus, particularly because its original description stated that its placement in Rattus is tentative. Rattus timorensis is known from a large fossil series on throughout Timor. There is another undescribed species of rat from Timor that is based on a single recently collected specimen. Monotypic. Distribution. Known only from type locality on W TimorI, Indonesia. Descriptive notes. Head—body 157 mm, tail 77+ mm, ear ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 842-843, DOI: 10.5281/zenodo.6887260 ...